2015
DOI: 10.1007/s10750-015-2288-z
|View full text |Cite
|
Sign up to set email alerts
|

Benthic cyanobacterial mats serve as a refuge and food for the amphipod Gammarus fasciatus

Abstract: We investigated the ecological role of Lyngbya wollei (Farlow ex Gomont, comb. nov.) cyanobacterial mats in aquatic ecosystems, especially as a food source and shelter for the amphipod Gammarus fasciatus (Say). For this, we offered amphipods a choice between mats of L. wollei and either chlorophytes (Spirogyra, Rhizoclonium) or an artificial mat made of acrylic wool in laboratory experiment. Moreover, we reconstructed in situ amphipod diet using a dual isotope mixing model (d 13 C and d 15 N). G. fasciatus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Although not quantified, pool macroalgae, which are dominated by Ulva spp 25 , may be more nutritious or palatable to the grazing metazoans than stromatolite microalgae. Preference for macroalgal species by macroinvertebrate grazers, depending on nutrient content, chemical defences or digestibility, have been observed in other intertidal environments 36 37 , although not necessarily consistently amongst ecosystems depending on the available producer species and consumer requirements 33 38 39 . Additionally, some authors have demonstrated the benefits provided to metazoans from microbialite habitats in terms of oxygen and predator refugia 22 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although not quantified, pool macroalgae, which are dominated by Ulva spp 25 , may be more nutritious or palatable to the grazing metazoans than stromatolite microalgae. Preference for macroalgal species by macroinvertebrate grazers, depending on nutrient content, chemical defences or digestibility, have been observed in other intertidal environments 36 37 , although not necessarily consistently amongst ecosystems depending on the available producer species and consumer requirements 33 38 39 . Additionally, some authors have demonstrated the benefits provided to metazoans from microbialite habitats in terms of oxygen and predator refugia 22 23 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Taxa populating these habitats must be able to cope with rapid irradiance alterations, high water-level fluctuations and monthslong drought periods. Moreover, a diverse assemblages of aquatic invertebrates, particularly amphipods like the small stygophilous spring dwelling Synurella ambulans (F. Müller, 1846), live on and within the microbial mats Thacker, 2006, 2013;Korpinen et al, 2006;Lévesque et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies addressing cyanobacterial and diatom communities in karst springs have examined mostly perennial streams, rarely springheads, and have ignored intermittent springs (Cantonati et al, 2012(Cantonati et al, , 2016. Their ecological role as the food source and shelter for freshwater invertebrates is still poorly understood (Camacho and Thacker, 2013;Lévesque et al, 2015). During high flow conditions specimens of the stygophilic amphipod S. ambulans are flushed to the surface of a temporary stream Krčić where they can be retained by the microbial mat and moss, thus preventing their drift and facilitating their successful retreat into underground in the periods of drought.…”
Section: Introductionmentioning
confidence: 99%
“…This study attempted to relate the metazoan community to resource availability, the pelagic resources being total suspended solids (reflecting phytoplankton biomass and detrital input), which would be important for filter feeders and detritivores (Miranda et al ). Benthic resources considered were stromatolite microalgae (both biomass and composition) and macroalgal cover, which provide food or habitat resources for benthic invertebrates (Lévesque et al ). Only macroalgal cover, predominantly comprised of Ulva spp.…”
Section: Discussionmentioning
confidence: 99%